An Efficient Visual Screen for CRISPR/Cas9 Activity in Arabidopsis thaliana - Hahn, Florian; Mantegazza, Otho; Greiner, André; Hegemann, Peter; Eisenhut, Marion; Weber, Andreas P. M. (Frontiers in Plant Science, 2017)
The CRISPR/Cas9 system enables precision editing of the genome of the model plant Arabidopsis thaliana (Arabidopsis) and likely of any other organism. Tools and methods for further developing and optimizing this widespread and versatile system in Arabidopsis would hence be welcomed. Here we designed a generic vector system that can be used to clone any sgRNA sequence in a plant T-DNA vector containing an ubiquitously expressed Cas9 gene. With this vector, we explored two alternative marker systems for tracking Cas9-mediated gene-editing in vivo: BIALAPHOS RESISTANCE (BAR) and GLABROUS1 (GL1). BAR confers resistance to glufosinate and is widely used as a positive selection marker; GL1 is required for the formation of trichomes. Reversion of a frameshift null BAR allele to a functional one by Cas9-mediated gene editing yielded a higher than expected number of plants that are resistant to glufosinate. Surprisingly, many of those plants did not display reversion of the BAR gene through the germline. We hypothesize that few BAR revertant cells in a highly chimeric plant likely provide system wide resistance to glufosinate and thus we suggest that BAR is not suitable as marker for tracking Cas9-mediated gene-editing. Targeting the GL1 gene for disruption with Cas9 provided clearly visible phenotypes of partially and completely glabrous plants. 50% of the analyzed T1 plants produced descendants with a chimeric phenotype and we could recover fully homozygous plants in the T3 generation with high efficiency. We propose that targeting of GL1 is suitable for assessing and optimizing Cas9-mediated gene-editing in Arabidopsis.